2013
DOI: 10.1111/j.1525-1594.2012.01565.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin‐1 Acutely Reduces the Permeability of Visceral Sheep Peritoneum In Vitro Through Both Endothelin‐A and Endothelin‐B Receptors

Abstract: Mesothelium is an important part of the peritoneal barrier for water and ion transport, essential for effective peritoneal dialysis (PD). Peritoneal fibrosis has been associated with PD treatment failure. Endothelin-1 (ET-1) is a potent vasoactive peptide, involved in pathologic fibrotic processes. Its action is mediated mainly by endothelin type A (ETA ) and type B (ETB ) receptors. The aim of this study was to investigate, by Ussing chamber experiments, the effect of ET-1 on the transmesothelial electrical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Whether peritoneal TJ abundance has an impact on peritoneal membrane transport characteristics is not yet proven. In leaky tissues TER reflects mainly the paracellular barrier, built by TJs and indirect evidence provided by electrophysiology experiments in sheep and human peritoneum suggest that its permeability is reflected by changes in the TER [ 36 , 37 , 38 ]. Based on mathematical modelling [ 34 ] and comparison of the electrophysiological monolayer characteristics of endothelial and mesothelial cells [ 29 ], the mesothelial cell layer presumably has limited barrier function as compared to the endothelial layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether peritoneal TJ abundance has an impact on peritoneal membrane transport characteristics is not yet proven. In leaky tissues TER reflects mainly the paracellular barrier, built by TJs and indirect evidence provided by electrophysiology experiments in sheep and human peritoneum suggest that its permeability is reflected by changes in the TER [ 36 , 37 , 38 ]. Based on mathematical modelling [ 34 ] and comparison of the electrophysiological monolayer characteristics of endothelial and mesothelial cells [ 29 ], the mesothelial cell layer presumably has limited barrier function as compared to the endothelial layer.…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo studies in sheep and human parietal peritoneum have shown that the transperitoneal permeability is reduced by vasogenic factors, such as epinephrine and endothelin-1, and that amiloride, a sodium channel blocker, has the same effect. Peritoneal permeability is defined by transcellular and paracellular pathways, with the latter being the predominant in cases of leaky membranes like the peritoneum [36][37][38]. Tight junctions (TJ) are the key paracellular barrier components of adjacent epithelial and endothelial cells, and control paracellular but also transcellular transport properties of the barrier indirectly.…”
Section: Introductionmentioning
confidence: 99%
“…Besides increased production of ET-1, Lebel et al found lower elimination of ET-1 via peritoneal membrane. [27][28][29][30][31] From our results, we concluded that imbalance in production of vasoactive substances (NO and ET-1) is present in CAPD patients. This imbalance can lead to disturbance in local blood flow control.…”
Section: Discussionmentioning
confidence: 94%
“…In other studies, 2,27 ETRs and insulin receptors within tissues were evaluated by the use of techniques such as the western blot assay, which requires the destruction of tissue structure. Although the western blot assay provides a better quantitative estimate of receptor expression, compared with that of immunohistochemical staining of tissues, it cannot provide information about receptor location within tissue.…”
Section: Discussionmentioning
confidence: 99%